If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(5k + 3) = -112 Reorder the terms: -4(3 + 5k) = -112 (3 * -4 + 5k * -4) = -112 (-12 + -20k) = -112 Solving -12 + -20k = -112 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -20k = -112 + 12 Combine like terms: -12 + 12 = 0 0 + -20k = -112 + 12 -20k = -112 + 12 Combine like terms: -112 + 12 = -100 -20k = -100 Divide each side by '-20'. k = 5 Simplifying k = 5
| 3n+16+5n+20=90 | | 81-y=8y-18 | | 7x-63=(-28) | | 6(y+3)=-2(4y-2)+8y | | 4/7×3 | | -3(5k+1)-k=61 | | b^2+20b-96=0 | | .6(x)+.33=1 | | (nm^-4/(2m^-2)^-3(2nm^2))^4 | | u+1=10 | | -4(5k+1)-k=61 | | 6(2f-12)+15-13f=-3 | | 6(3-x)-5x=-4 | | (2-x)(2+x)+(x+3)(x+3)=x-7 | | 5x+13+12x+1=37 | | 8x-62=3x+18 | | -76-5x=-12x+57 | | 10x-3=13x+97 | | 9+3=6 | | 5a-18=-27 | | x=66000+0.07x | | 2y+4-t+3= | | -4x-81=-8x+31 | | -62+12x=2x+138 | | 0=4x^3-6x^1/2 | | 6(3x-8)=24 | | -7(h-4)+12h=38 | | (2-x)(2+x)+(x+3)(x+3)=x+7 | | 5f-3h+4f-2g+2f= | | -50+9x=4x+20 | | 9p+4-13p=-28 | | 1/2x0 |